The Injection of Air/Oxygen Bubble into the Anterior Chamber of Rabbits as a Treatment for Hyphema in Patients with Sickle Cell Disease - Emre Ayintap; Uğurcan Keskin; Fariz Sadigov; Mesut Coskun; Nilufer İlhan; Sedat Motor; Hilal Semiz; Nihan Parlakfikirer (Journal of Ophthalmology)
Purpose. To investigate the changes of partial oxygen pressure (PaO2) in aqueous humour after injecting air or oxygen bubble into the anterior chamber in sickle cell hyphema. Methods. Blood samples were taken from the same patient with sickle cell disease. Thirty-two rabbits were divided into 4 groups. In group 1 (n=8), there was no injection. Only blood injection constituted group 2 (n=8), both blood and air bubble injection constituted group 3 (n=8), and both blood and oxygen bubble injection constituted group 4 (n=8). Results. The PaO2 in the aqueous humour after 10 hours from the injections was 78.45 ± 9.9 mmHg (Mean ± SD) for group 1, 73.97 ± 8.86 mmHg for group 2, 123.35 ± 13.6 mmHg for group 3, and 306.47 ± 16.5 mmHg for group 4. There was statistically significant difference between group 1 and group 2, when compared with group 3 and group 4. Conclusions. PaO2 in aqueous humour was increased after injecting air or oxygen bubble into the anterior chamber. We offer to leave an air bubble in the anterior chamber of patients with sickle cell hemoglobinopathies and hyphema undergoing an anterior chamber washout.